Estimasi Output Sapi Potong di Lahan Pasang Surut Kabupaten Banyuasin Provinsi Sumatera Selatan - Aulia Evi Susanti; Nono Ngadiyono; Sumadi Sumadi (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2015)
Tidal lowland are one of the potential for development of agro-ecosystem farm. Banyuasin have a fairly extensive wetlands. Data on livestock productivity in Banyuasin yet available. The aim of the study was to identify the output of beef cattle in Banyuasin regency, South Sumatra province. This research was conducted from July to October 2014 in 3 districts. One thousand one hundred eighty traditional breeders were involved in this research and interviewed on cows reproduction characteristics and breeding management. Data cows reproduction characteristic was analyzed with the average and standard deviation and estimation output was calculated using breeding teory. The results of research showed that efficiency valued reproduced 98.27%, natural increase 24.39%, male net replacement rate 143.26% and female 220.15% and estimation output was 24.30% equal to 7.267 heads.